Outstanding representative of Azerbaijani sculpture - Omer Eldarov - Sevil Bayram qızı Əliyeva, (Theoretical Hypotheses and Empirical Results, 2024)
The outstanding sculptor Omar Eldarov, who has his own rich inner world, is a genius who created unforgettable images. The first signs of the emergence of this style appeared at the end of the 19th century. Architects gave up stone and wood and succeeded in creating large-scale buildings thanks to the use of glass, iron and concrete constructions. Will and elegance, improvisation and perfection, depth and the ability to feel are the main things that accompany Omar Eldarov's creativity. The influence of his creativity on the artistic environment of our country cannot be underestimated. The harmony of the inner content and form in the sculptor's works prompts a person to think involuntarily. The sculptures created by Omar Eldarov always attract attention with their dynamism. The courage, optimism and moral responsibility inherent in his character are embodied in the artist's work, especially in the artistic expression of images.